(NlINEJNAQ ALGEBRA I NEKOTORYE EE PRILOVENIQ (B:s (Nu^EBNOE POSOBIE (B/s - (NgOLOWINA(B, (NlIDIQ iWANOWNAs ((NmOSKWA (B:s (NnAUKA(B. (NgL(B. (NRED(B. (NFIZ(B.-(NMAT(B. (NLIT(B.,s, 1975)
(NbIBLIOGR(B. 34 (NNAZW(B.s
Keywords: (NlINEJNAQ ALGEBRAs